(1E,4E)-1-(2-Nitrophenyl)-5-(2,6,6-trimethylcyclohex-1-en-1-yl)penta-1,4-dien-3-one - Zou, Peng (International Union of Crystallography, 2012)
In the title curcumin–ionone derivative, C(20)H(23)NO(3), the dihedral angle between the cyclohexene and benzene rings is 21.03 (8)°, with both double bonds in the interlinking olefinic chain adopting E conformations. Two of the methylene groups of the β-ionone ring are disordered over two sets of sites with occupancy ratios of 0.50:0.50 and 0.60:0.40. In the crystal, molecules are linked by weak C—H⋯O hydrogen bonds into zigzag chains extending along the b axis.